Liver fibrosis and retinal features in an older Mediterranean population: Results from the Salus in Apulia study - Lampignano, Luisa; Niro, Alfredo; Castellana, Fabio; Bortone, Ilaria; Zupo, Roberta; Tirelli, Sarah; Tatoli, Rossella; Griseta, Chiara; De Nucci, Sara; Sila, Annamaria; De Pergola, Giovanni; Conte, Caterina; et al. (Frontiers in Neuroscience, 2022)
Background Age is a leading contributor to the liver fibrosis rate and a gradual deterioration of optical function, but this association in older populations is still under-explored. The present study aimed to explore the link between vascular and neural retinal characteristics and the risk of liver fibrosis in 731 older adults from the population-based Salus in Apulia study. Methods Retinal features were obtained using optical coherence tomography (OCT) and OCT-angiography (OCT-A). Liver fibrosis risk was taken as the fibrosis-4 (FIB-4) score. Generalized linear models (logistic regression) were used to estimate the association effect between each unit increase of OCT and OCT-A parameters as independent variables and a FIB-4 >= 2.67 score as an outcome. Generalized additive models were used to assess the non-linear association between OCT-A features and the linear FIB-4 score. Results Increased gangliar cell complex (GCC) thickness was inversely associated with a FIB-4 score above the cut-off in both the raw model (OR: 0.98; 95% CI: 0.96–0.99; SE: 0.01) and after adjustment for age, sex, education, hypertension, diabetes, total cholesterol and triglycerides (OR: 0.98; 95% CI: 0.97–0.99; SE: 0.01). Conclusions Our findings add to the growing volume of scientific literature demonstrating that liver fibrosis is associated with neurodegeneration. This study raises a number of new questions, including whether OCT-a may be used to track the progression of retinal abnormalities and define exact thresholds for predicting and classifying liver disease.